2016
DOI: 10.1016/j.jdent.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Integration of oral health-related quality of life instruments

Abstract: Objectives To integrate items from two widely used oral health-related quality of life (OHRQoL) questionnaires, the General Oral Health Assessment Index (GOHAI) and the Oral Impacts on Daily Performances (OIDP), as well as culturally-specific items of the Oral Health Impact Profile (OHIP) into a four-dimensional OHRQoL model consisting of Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact. Methods Subjects came from an ancillary study of the Dimensions of Oral Health-Related Quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 27 publications
4
64
0
2
Order By: Relevance
“…This dPRO has four dimensions: Oral Function, Orofacial Pain, Orofacial Appearance and Psychosocial Impact (John, Feuerstahler, et al, ; John, Reissmann, et al, ; John, Rener‐Sitar, et al, ). Oral Function, together with the other three dimensions, was investigated for the Oral Health Impact Profile (Slade & Spencer, ); however, the four dimensions were found to be applicable also to other oral health‐related quality of life instruments (John, Reissmann, et al, ). In a systematic review targeting dPROs and the measures they assess (John, ), it could be shown that jaw functional limitations is a similar dPRO compared to Jaw Functional Status, Functional Limitations, Mandibular Function Impairment etc.—all of them targeting the dPRO Oral Function (Mittal et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This dPRO has four dimensions: Oral Function, Orofacial Pain, Orofacial Appearance and Psychosocial Impact (John, Feuerstahler, et al, ; John, Reissmann, et al, ; John, Rener‐Sitar, et al, ). Oral Function, together with the other three dimensions, was investigated for the Oral Health Impact Profile (Slade & Spencer, ); however, the four dimensions were found to be applicable also to other oral health‐related quality of life instruments (John, Reissmann, et al, ). In a systematic review targeting dPROs and the measures they assess (John, ), it could be shown that jaw functional limitations is a similar dPRO compared to Jaw Functional Status, Functional Limitations, Mandibular Function Impairment etc.—all of them targeting the dPRO Oral Function (Mittal et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…30 Thereby, singular items of the OHIP-G14 questionnaire can be assigned to these categories within a four-dimensional OHRQoL model. 30 Thereby, singular items of the OHIP-G14 questionnaire can be assigned to these categories within a four-dimensional OHRQoL model.…”
Section: Comparison With Published Datamentioning
confidence: 99%
“…The QoL is a complex concept, and the same instruments can have differently grouped items for various cultural surroundings, and a multidimensional structure can be reduced when explored on a large international sample . Therefore, the new characterization of psychosocial dimensions emerged, such as Aesthetic Attitude or Orofacial Appearance . Recently, efforts have been made into the process of integration of existing OHRQoL instruments in order to develop a simpler, yet psychometrically improved measurement …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the new characterization of psychosocial dimensions emerged, such as Aesthetic Attitude or Orofacial Appearance . Recently, efforts have been made into the process of integration of existing OHRQoL instruments in order to develop a simpler, yet psychometrically improved measurement …”
Section: Discussionmentioning
confidence: 99%